THE STANDARD OF LIVING OF FAMILIES WITH CHILDREN IN THE REPUBLIC OF TATARSTAN: PROBLEMS OF MEASUREMENT AND IMPROVEMENT - Natalya Valerievna Ivanova (Science and Innovation Center Publishing House, 2020)
The article analyzes the social indicators of the standard of living of families with children in the Republic of Tatarstan, published by official statistics. The measures of social support for families with children are systematized according to the criteria of the need of families.